Consecutive Methylation Catalyzed by TsrM, an Atypical Class B Radical SAM Methylase. Issue 14 (16th May 2022) - Wu, Runze; Ding, Wei; Zhang, Qi
Comprehensive Summary: TsrM is a cobalamin‐dependent radical S‐adenosylmethionine (SAM) methyltransferase belonging to the Class B radical SAM methylase (RSM) family. This enzyme catalyzes the C‐2 methylation of L ‐tryptophan to produce 2‐methyltrytophan (2‐MeTrp), an intermediate involved in the biosynthesis of thiostrepton A. In this work, we report characterization of an unexpected activity of TsrM, which carries out an additional methylation reaction on the product 2‐MeTrp. A series of isotopic labeling studies and assays with different Trp analogs revealed that TsrM is able to transfer a methyl group from SAM to the C4 of 2‐MeTrp to produce 2, 4‐dimethyltryptophan. These results reveal the intriguing substrate specificity of TsrM, further expanding the reaction promiscuity of the radical SAM superfamily enzymes. Abstract :